Real-time observation of the intravalley spin-flip process in single-layer WS2 - Wang Zilong; Molina-Sanchez Alejandro; Altmann Patrick; Sangalli Davide; De Fazio Domenico; Soavi Giancarlo; Sassi Ugo; Bottegoni Federico; Ciccacci Franco; Finazzi Marco; Wirtz Ludger; Ferrari Andrea; et al. (EPJ Web of Conferences, 2019)
We use helicity-resolved transient absorption spectroscopy to track intravalley scattering dynamics in monolayer WS2. We find that spin-polarized carriers scatter from upper to lower conduction band by reversing their spin orientation on a sub-ps timescale.